The Semantic Organization of the Serbo-Croatian Verb - Gorup, Radmila J. (1987)
This work presents a re-analysis of a major segment of the paradigm of the Serbo-Croatian verb. It concentrates chiefly on the perfective and imperfective morphology, but treats this classic problem in Slavic scholarship from a non-aspectual point of view.